IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 2 TAHUN 2016 TENTANG KARTU IDENTITAS ANAK DI KANTOR DINAS KEPENDUDUKAN CATATAN SIPIL KABUPATEN BANYUASIN - Haryani, Deffi (STIA SATYA NEGARA PALEMBANG, 2023)
This study aims to analyze how the implementation of the Minister of Home Affairs RegulationNumber 2 of2016 concerning Child Identity Cards at the Office of the Civil Registry Office of Banyu asin Regency (CaseStudy ofBanyuasin IIIDistrict, BanyuasinRegency) This study uses qualitative research methods, data collection techniques using observation, interviews,documentation and literature study. The findings of this study at the Banyuasin Sub-district Office incarrying out six implementation indicators, namely policy standards and targets, Resources, Inter-organizational communication, Characteristics of implementing agents, Economic, social and politicalenvironment and the attitude of the implementers are good enough so that the quality of service isincludedin agood category. in implementation. Based on the results of research and discussion of the findings of researchers in the field regarding theimplementation of the Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards at the Office of Population and Civil Registration of Banyuasin Regency (CaseStudyofBanyuasin District III, Banyuasin Regency) has not been fully implemented properly because there isstill a lack of socialization- direct socialization in a persuasive manner to the community so that thereare still people who do not understand the use and importance of this child identity card and have not achieved the target in making child identity cardsin Banyuasin III District. Keywords: Implementation, Child Identity Card